Blue-yellow colour vision in an onchocercal area of northern Nigeria. Issue 5 (1st May 1998) - Landers, A; Murdoch, I E; Birch, J; Cousens, S N; Babalola, O E; Lawal, B; Abiose, A; Jones, B R
Abstract : AIM: To determine if the City University Tritan Test is a useful addition to visual function assessment in rural communities in northern Nigeria. METHODS: The study was a cross sectional survey. The participants were 8394 people, aged 5 years and over, living in 37 rural communities, mesoendemic and non-endemic for onchocerciasis, in Kaduna State in northern Nigeria. The main outcome measures were the detection of a defect in blue-yellow colour vision by two criteria: (1) failure with the City University tritan screening plates; (2) failure with the City University grading plates to identify severe tritan defects. RESULTS: 91% of those aged 10 years and above could perform the test. Below this age, there were difficulties in comprehension. The test showed good inter- and intraobserver agreement. After adjustment for confounders the odds of failing the screening plates were significantly increased in the presence of optic atrophy or glaucoma (3.55 (2.48–5.08) and 15.9 (4.22–60.2) respectively). There was a greater increase in the adjusted odds of failing the grading plates in the presence of optic atrophy or glaucoma (5.30 (2.97–9.45) and 8.87 (1.61–48.7) respectively). Cataract had a smaller effect on the screening plates, adjusted odds 1.63 (0.95–2.80). CONCLUSION: Blue-yellow colour vision testing is a useful addition to visual function assessment in those aged 10 years and above in rural northern Nigeria, particularly in the detection of optic nerve disease.